PELATIHAN TEKNOLOGI 3D PRINTING BAGI GURU SMK KRISTEN NUSANTARA KUDUS UNTUK MENDUKUNG KOMPETENSI KEAHLIAN DI ERA INDUSTRI 4.0 - Bellachintya Reira Christata; Rangga Primadasa; Adhie Prayogo (Jurnal Abdi Insani, 2026)
The development of additive manufacturing technology, particularly 3D printing, requires vocational schools to adapt to the demands of the digital-based industry. However, the utilization of this technology at the vocational high school (SMK) level remains limited due to insufficient teacher competencies and supporting facilities. SMK Kristen Nusantara Kudus, as a partner institution, requires capacity strengthening of productive subject teachers to enable them to integrate 3D printing into the learning process. Therefore, a structured and practical training program is necessary. This community service activity aims to enhance the competence of productive teachers in understanding and operating 3D printing technology and integrating it as a learning medium as well as a support for entrepreneurship based on additive manufacturing. The implementation method consists of initiation and preparation stages, socialization, training, mentoring, and sustainability stages. The materials include an introduction to additive manufacturing concepts, the slicing process, and hands-on practice in printing simple objects using a 3D printer. The implementation results indicate an improvement in teachers’ understanding of the basic concepts of additive manufacturing and the 3D printing workflow, from design to final product. Participants’ enthusiasm was reflected in their active engagement during discussions and hands-on practice sessions. Teachers also began identifying potential integration of 3D printing into productive subjects and exploring opportunities for developing creative products aligned with school-based entrepreneurship initiatives. This program strengthens the school’s readiness to adopt digital-based learning technologies. The effectiveness of the 3D printing training in improving teacher competence and supporting the integration of additive manufacturing technology in vocational schools is evidenced by questionnaire results